SOYBEAN GROWTH AND YIELD WITH APPLICATION OF PHOSPHATE FERTILIZER AND ORGANIC MATTER - Nasution, Lely Wahidah; Hanum, Chairani; Hanum, Hamidah (Universitas Negeri Medan, 2017)
AbstractSoybean is useful for tofu, tempe, soy sauce and soy milk. The effective use of fertilizer and organic application can increase soybean productivity. The objective of this research was to study the growth and yield of various soybean varieties on application of phospate fertilizer and organic matter. This research was conducted in North Binjai and Research and Technology Laboratory Agriculture Faculty Universitas Sumatera Utara, Medan on May-September 2016. The method used Randomized Block Design with 3 factors. The first factor is soybean varieties consisting of: (Argomulyo, Dering, Dena, Kaba, Gema, Grobogan and Wilis), fertilization of phosphate (control and 150 kg/ha) and organic material application (control, Blotong 10 ton/ha and POEFBC/Palm Oil Empty Fruit Bunches Compost 10 ton / Ha). The results of this research showed that the seven varieties of soybean had characteristic differences on shoot dry weight, age of flowering, age of harvest, phospate uptake and dry weight of 100 seed. The longest flowering and harvesting age is obtained in Wilis, while the shortest age is Grobogan. The highest uptake of P in Argomulyo with treatment without organic matter and phospate fertilizer. Kaba variety with blotong treatment has the highest dry seed weight.Keywords : Organic Matter, Phosphate Fertilizer, Soybean Varieties